2007
DOI: 10.1603/0022-2585(2007)44[799:oaoeho]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Ovicidal Activity of Entomopathogenic Hyphomycetes on <I>Aedes aegypti</I> (Diptera: Culicidae) Under Laboratory Conditions

Abstract: The ovicidal activity of 21 hyphomycete fungi species against Aedes aegypti (L.) (Diptera: Culicidae) was tested. Fungi with ovicidal activity developed on high numbers of eggs (> or =70%) during 25 d of exposure. A clear ovicidal activity with low values of hatch (1.3-40%) was observed after 25 d of incubation with Isaria farinosa (Holm: Fries) Fries, Paecilomyces carneus (Duché & Heim) Brown & Smith, Paecilomyces marquandii (Massee) Hughes, Isaria fumosorosea (Wize), Metarhizium anisopliae (Metschnikoff) Sor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
50
0
3

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 2 publications
0
50
0
3
Order By: Relevance
“…Beauveria bassiana was grown on Czapek Dox media modified with maize flour as per findings of Ramle et al [15] and on Sabouraud-dextrose media with yeast extract [16] for growth optimization of the entomopathogenic fungus. Once the fungus was identified [17], pure cultures were obtained followed by flask cultures to develop the fungal mat.…”
Section: Culturementioning
confidence: 99%
“…Beauveria bassiana was grown on Czapek Dox media modified with maize flour as per findings of Ramle et al [15] and on Sabouraud-dextrose media with yeast extract [16] for growth optimization of the entomopathogenic fungus. Once the fungus was identified [17], pure cultures were obtained followed by flask cultures to develop the fungal mat.…”
Section: Culturementioning
confidence: 99%
“…Moreover, eggs out of water resist prolonged desiccation during distinct dry seasons, and the surviving larvae contribute to a reestablishment of vector populations at the beginning of the rainy season, thus increasing the risk of dengue epidemics (Sota & Mogi 1992, Silva & Silva 1999. Inside eggs, diapausing larvae are exposed to predation and infection by pathogens, particularly fungi that may invade eggs actively through the egg shell or affect larvae with toxic metabolites produced on the egg surface (Russell et al 2001, Luz et al 2007). Moisture is a limiting factor for both egg survival and fungal activity but there is still little information about the impact of relative humidity (RH) on the survival of larvae inside eggs or a possible effect of entomopathogenic fungi.…”
mentioning
confidence: 99%
“…This fungal species is pathogenic to larvae and adults of A. aegypti (Scholte et al 2004, Silva et al 2004, and recent studies indicated that it is also effective against eggs of this vector (Luz et al 2007). The fungal isolate tested here, IP 46, originated from a soil sample collected in 2001 in the Cerrado of Central Brazil and was stored at the IPTSP, UFG, Goiânia, Brazil.…”
mentioning
confidence: 99%
See 2 more Smart Citations